A novel and efficient method for the direct synthesis of pyrrolyl or indolyl substituted 9, 10-dihydrophenanthren-9-ol analogues. Issue 7 (13th February 2020) - Xia, Qi; Zhao, Xinlei; Zhang, Juan; Wang, Jiayi; Song, Gonghua
Graphical abstract: Highlights: A domino intramolecular [3+2] cycloaddition and ring-opening aromatization process. Direct synthesis of pyrrolyl or indolyl substituted 9, 10-dihydrophenanthren-9-ol analogues. Compound anti -4jb displayed a lowest IC50 value of 9.99 μM (24 h) against HepG2 cells. Abstract: A novel domino intramolecular [3+2] cycloaddtion and ring-opening aromatization process has been successfully developed for the efficient direct synthesis of pyrrolyl or indolyl substituted 9, 10-dihydrophenanthren-9-ol analogues. And 1-(phenanthren-9-yl)-1H-pyrroles can be easily obtained via dehydration of 10-(1H-pyrrol-1-yl)-9, 10-dihydrophenanthren-9-ols. Furthermore, the MTT assay indicated that four compounds with indolyl substitutions showed obvious inhibitory activities against HepG2 cells, and compound anti-4jb displayed a lowest IC50 value of 9.99 μM.